Returning to sport following COVID-19: Considerations for heat acclimatization in secondary school athletics - Adams, W. M.; Périard, J. D. (Sports Medicine, 2020)
The cataclysmic events that have taken place across the globe as a result of the COVID-19 pandemic have infiltrated every aspect of society, including sport. As many places around the world are either beginning to observe or are on a downward descent of "flattening of the curve", local, regional/state and national leaders have initiated steps to lift various stay-at-home orders and resume normal activities. With the recommencement of sanctioned athletic events over the upcoming summer months within the Northern Hemisphere, increased caution must be taken by clinicians, administrators, coaches and other stakeholders to ensure that proper procedures are in place to reduce the risk of injury, particularly at the secondary school level. The prolonged dormancy of secondary school student-athletes as a result of the current global pandemic, in combination with extreme heat observed during the summer months, also places these individuals at increased risk of exertional heat stroke (EHS), thus necessitating increased scrutiny toward optimizing EHS-related risk-reduction strategies.